Subjective norms and social media: predicting ethical perception and consumer intentions during a secondary crisis. Issue 1 (2nd January 2023) - Brock Baskin, Meagan E.; Hart, Timothy A.; Bajaj, Akhilesh; Gerlich, R. Nicholas; Drumheller, Kristina D.; Kinsky, Emily S.
ABSTRACT: When firms face crisis, the instant and open channels of social media communication create a double-edged sword. While corporations can more quickly communicate with stakeholders, any missteps will have drastic and nearly immediate repercussions. What are the relationships among social media, subjective norms, attitudes, and intentions during corporate crisis? We explore this phenomenon via a study of a crisis faced by Lowe's, an international home improvement store, and how current and potential customers reacted. By utilizing a structural equations model to examine an integrated model of multiple constructs, we find that Facebook usage is associated with behavioral intent, perceptions of ethicality, and attitudes toward the organization. Counter intuitively, we find that an increase in participant Facebook usage is negatively related to felt subjective norms. Our findings indicate that beyond the traditional relationships examined by the Theory of Reasoned Action (e.g., norms, attitudes, and behavioral intent), that social media and subjective norms have a strong relationship with general attitudes and ethical attitudes toward an organization.